(untitled) (Research, Society and Development, 2022)
The increase in life expectancy of the Brazilian population has revealed a new reality of a significant increase in the elderly population, which represents a challenge for public health. As an alternative, the admission of the elderly to Long Stay Institutions for the Elderly (ILPI) is not always voluntary and involves many feelings and cognitions. Therefore, the objective of this study is to understand the socioeconomic profile and analyze the view of the elderly in the new life cycle in an ILPI in Jaboatão dos Guararapes-PE. This is a descriptive study with a quali-quantitative method, in which a semi-structured socioeconomic questionnaire was applied that contained guiding questions about the experience at the ILPI. The results showed that most of the elderly in these institutions were male, aged between 80-90, divorced. Although most elderly women reported being single. Most had an income of one minimum wage. Most participants declared themselves Catholic and all claimed to have some religious belief. The elderly reported receiving regular visits, mostly from family members. Most were allocated to the ILPI by the family’s decision and some by their own decision, the most common reason being that families have difficulty maintaining them due to lack of resources or structure. Although most institutionalized patients had a positive view of their life at the ILPI, reports of loneliness, homesickness, independence, and privacy were observed. The vision of the elderly in LSIEs are important guides for improving service provision and quality of life in these environments of great social responsibility.